(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2025)
This article briefly presents an analysis of costume design thinking throughout the historical and expressive changings of the western theater, which oscillates between the transformation and the transfiguration of the body on stage. To organize a systematic observation of these changes, I propose a diagram that outlines these possibilities of creation, ranging from the characterization through costume design and accessories to the performative use of these same materialities. This diagram structures the conceptual and practical expansion of costume design within a historical framework and serves as a pedagogical tool to analyze and to apply procedures for emerging artists of the scenic arts